Paleomagnetism of the Late Cretaceous Red Beds From the Far Western Lhasa Terrane: Inclination Discrepancy and Tectonic Implications. Issue 8 (8th August 2020) - Bian, Weiwei; Yang, Tianshui; Jiang, Zelei; Jin, Jingjie; Gao, Feng; Wang, Suo; Peng, Wenxiao; Zhang, Shihong; Wu, Huaichun; Li, Haiyan; Cao, Liwan; Deng, Chenglong
Abstract: The precollisional locations and geometries of the Lhasa terrane (LT) are critical to constrain the India‐Asia collision. However, the inclinations of the Cretaceous paleomagnetic data obtained from the northern limb of folds are obviously lower than those obtained from the southern limb, which cause large discrepant paleolatitudes of the LT prior to India‐Asia collision. Here, we carried out a new paleomagnetic investigation on the Late Cretaceous Jingzhushan Formation red beds in the far western LT. The tilt‐corrected site mean direction yielded a palaeopole at 74.4°N, 226.0°E with A95  = 3.8° ( N  = 54). This paleomagnetic data set passes fold tests and indicates that the studied area was located at 19.6° ± 3.8°N during the Late Cretaceous. However, the mean inclination calculated from the northern limb of folds ( I s  = 19.0°) is significantly lower than that of the southern limb of folds ( I s  = 51.8°). This inclination discrepancy of the Jingzhushan Formation red beds may be attributed to the syntectonic sedimentation. Nevertheless, the site mean direction obtained from both limbs of folds is generally consistent with the site mean direction after syntectonic‐sedimentation correction. Our new paleomagnetic results, combined with the reliable Cretaceous paleomagnetic results from the LT showed that the southern margin of Asia had a present‐day relatively east‐west alignment prior to India‐Asia collision. Key Points: A new paleopole (74.4°N, 226.0°E with A95  = 3.8°) was obtained from the Jingzhushan Formation red beds in the far western Lhasa terrane Inclination discrepancy of the Jingzhushan Formation red beds may be attributed to the syntectonic sedimentation The southern margin of Asia had a present‐day relatively east‐west alignment prior to India‐Asia collision